FAKTOR-FAKTOR YANG MEMPENGARUHI EARNINGS RESPONSE COEFFICIENT (ERC) - Subagyo .; Cicilia Novita Olivia (Jurnal Akuntansi, 2012)
Publication of financial statements through the mass media can influence an investment decision prospective investors. This is due to the information contained in financial statements is considered the latest news about the state of the company in the capital market. Reflection of the ERC depends on the "good news or" bad news "contained in the earnings. ERC showed that high earnings are able to provide information to investors in making economic decisions. Instead the low ERC suggests that earnings are less informative for investors to make economic decisions. This study will examine whether the variable leverage, growth, audit opinion, audit firm reputation, size, and earnings classification can affect earnings response coefficient (ERC). This study found that size and leverage have a negative and significant impact on earnings response coefficient. In addition, this study also found that the audit firm's reputation has a positive and significant impact on earnings response coefficient.Â Keyword: leverage, growth, audit opinion, audit firm reputation, size, earnings classification, earnings response coefficient (ERC).